Recent Publications (Quarterly Journal of Economics, 1938)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 52, Issue 3, May 1938, Pages 541–546, https://doi.org/10.1093/qje/52.3.541 Published: 01 May 1938